Peer review of the pesticide risk assessment of the active substance dichlorprop‐P and variant dichlorprop‐P‐2‐ethylhexyl - European Food Safety Authority (EFSA); Maria Arena; Domenica Auteri; Stefania Barmaz; Alba Brancato; Daniela Brocca; Laszlo Bura; Luis Carrasco Cabrera; Arianna Chiusolo; Consuelo Civitella; Daniele Court Marques; Federica Crivellente; et al. (EFSA Journal, 2018)
Abstract The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State Ireland and co‐rapporteur Member State Poland for the pesticide active substance dichlorprop‐P and the variant dichlorprop‐P‐2‐ethylhexyl and the assessment of applications for maximum residue levels (MRLs) are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative uses of dichlorprop‐P as a herbicide on cereals, grassland and grass seed crops and of the variant dichlorprop‐P‐2‐ethylhexyl as a plant growth regulator on citrus. MRLs were assessed in mandarin and lemon. The reliable end points, appropriate for use in regulatory risk assessment and the proposed MRLs, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.